Centralized surveillance of hydatidiform mole: 7-year experience from a regional hospital in China. Issue 2 (19th November 2021) - Jiao, Lanzhou; Wang, Yaping; Jiang, Jiyong; Wang, Xiuying; Zhang, Wenqing; Zhu, Chenggong; Xiang, Yang
Abstract : Objective: To assess the strategy and value of centralized surveillance of hydatidiform mole at a regional hospital in China and to investigate the necessity of prophylactic chemotherapy for high-risk complete hydatidiform mole. Methods: Between February 2013 and February 2020, all women with hydatidiform mole in Dalian Women's and Children's Medical Center (Group) were registered for surveillance and treatment when indicated. Women with complete hydatidiform mole were categorized into low-risk and high-risk groups according to the criteria from Song Hongzhao's trophoblastic neoplasia. Outcomes and treatments were analyzed retrospectively. Results: In total, 703 women with hydatidiform mole were registered for surveillance with a follow-up rate of 97.9% (688/703). 680 women were enrolled and 52 (7.6%) developed post-molar gestational trophoblastic neoplasia, all with low-risk International Federation of Gynecology and Obstetrics (FIGO) scores 0–5. Post-molar gestational trophoblastic neoplasia was diagnosed in 12.3% (51/413) of patients with complete hydatidiform moles and 0.4% (1/263) of patients were diagnosed with partial hydatidiform moles (χ 2 =32.415, p<0.001). Post-molar gestational trophoblastic neoplasia was diagnosed in 27.7% (28/101) of the high-risk complete hydatidiform mole group and in 7.4% (23/312) of the low-risk complete hydatidiform mole group (χ 2 =29.196, p<0.001). No difference in the pre-treatment assessments of patients with post-molar gestational trophoblastic neoplasia was found between the low-risk and high-risk complete hydatidiform mole groups (all p>0.05). All 52 patients with post-molar gestational trophoblastic neoplasia were cured, with a complete response rate of 61.2% (30/49) with first-line single-agent chemotherapy. Conclusions: A centralized hydatidiform mole surveillance program is feasible and effective and may improve the prognosis of patients with post-molar gestational trophoblastic neoplasia. Prophylactic chemotherapy is not recommended for women with high-risk complete hydatidiform mole with adequate surveillance.